편백 정유향의 흡입이 주의집중력과 기분상태의 변화에 미치는 영향 - 성현수; 고유라; 최인화 (Journal of forest and environmental science , 30(1), 2014)
The principle purpose of this research is to figure out whether the inhalation of Wood Essential oil (Chamaecyparis obtusa) affect not only human beings' concentration for surroundings but also change as to status of feelings. total number of subjects for this experimental are determined to be 66 (men 44 and women 22) among 85 adults who agreed to participate in this experiment after excluding 19 participants who were not able to smell scent due to flu and nasal inflammation. After both experimental group and control group being measured referring to their status of mood such as concentration, depression, vigor, fatigue, confusion, tension and anger, the experimental group is offered to get a piece of cotton that includes Wood Essential oil and they are asked to inhale it for 5 min. On the other hand, control group is offered to wait for the experimental group finishing inhaling wood Essential oil for 5 min. After 5 min, the status of mood from both groups were measured again. simultaneously, I conducted a survey targeting experimental group to see what their preferences are like regarding scent of wood essential oil. The experiment shows that the status of experimental group's concentration is improved about 0.94 point when compared to control group's. Moreover, Total mood disturbance is lower than control group's. Therefore it is proved that the inhalation of wood Essential oil alleviates overall status of mood. according to the analyses result of favor to scent for wood essential oil from experimental group, some of them who were positive got much better improvement when it comes to concentration and far more relieved on their feelings than those who weren't. Based from this result, it is definitely confirmed that there is a Phytoncide‘s psychophysiological effect which transcends the Placebo Effect generated by Phytoncide’s positive image. KCI Citation Count: 8